Art Autonomy and its Truths. Modern Aesthetic purism and contemporary artistic pluralism - Domínguez Hernández, Javier (Estudios de Filosofía, 2000)
The concept of Autonomy of Art has always been controversial. As for the Modern idea of art, autonomy was sometimes understood as the sovereignty of a particular concept of art, excluding any other. This idea became so radical that when it entered in crisis in the nineteenth eighties, it propitiated mottoes such as "The death of art" in a time when, paradoxically, art showed a great vitality in its different forms. These contradictions have lead to differentiate Modem Art and Contemporary Art, and have also induced redefining Autonomy in terms of Artistic pluralism.